Demographic Incidence of Recumbent Cow Syndrome in Cauvery Delta Region of Tamil Nadu, India - A, Thamizharasi; M, Veeraselvam; N, Premalatha; Senthilkumar S; Karthika K; Saravanan M; Ramkumar P K (Indian Journal of Veterinary Medicine, 2024)
This study investigates the demographic incidences of recumbent cow syndrome in 156 recumbent cows over a period of 9-month in the Cauvery Delta region of Tamil Nadu, India. They were examined & categorized based on breed, age, and period of occurrences. The incidence of recumbent cow was higher incidences during May month and lower during November month. Whereas the highest incidence of recumbent cow syndrome was noticed in Jersey cross bred cow (69.8%) followed by Holstein Friesian cross bred (25.0%) and native breeds (5.1%) whereas higher incidence of recumbent cow syndrome was observed in cows with the age group of 6 to 8 years. These findings emphasize the need for targeted management strategies to address this challenging metabolic disorder in dairy farming, considering specific time period or season, breeds, and age groups.